2002
DOI: 10.1074/jbc.m108360200
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide and cGMP-dependent Protein Kinase Regulation of Glucose-mediated Thrombospondin 1-dependent Transforming Growth Factor-β Activation in Mesangial Cells

Abstract: Excessive transforming growth factor-␤ (TGF-␤) activity in hyperglycemia contributes to the development of diabetic nephropathy. Glucose stimulation of TGF-␤ activity and matrix synthesis are dependent on autocrine thrombospondin 1 (TSP1) to convert latent TGF-␤ to its biologically active form. The mechanisms by which glucose regulates TSP1 are not known. High glucose inhibits nitric oxide (NO) bioavailability and decreased NO increases TGF-␤ activity and extracellular matrix accumulation. Yet, the impact of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 54 publications
8
63
1
Order By: Relevance
“…This observation is consistent with the results of Wang et al (2002). Our results further demonstrate that different NO donors act in a time-and concentration-dependent manner to prevent increases in steady-state TSP-1 mRNA.…”
Section: Bereitgestellt Von | Universitaetsbibliothek Der Lmu Muenchensupporting
confidence: 82%
“…This observation is consistent with the results of Wang et al (2002). Our results further demonstrate that different NO donors act in a time-and concentration-dependent manner to prevent increases in steady-state TSP-1 mRNA.…”
Section: Bereitgestellt Von | Universitaetsbibliothek Der Lmu Muenchensupporting
confidence: 82%
“…Inhibition could be reversed by treating cells with the sGC inhibitor 1H- [1,2,4]oxadiazole [4,3-a]quinoxalin-1-one (ODQ, IC 50 = 20 nM). This is consistent with the finding that inhibition of glucose-induced TSP1 expression in mesangial cells by an NO donor was reversed by ODQ and by the inhibitor of cGMP-dependent protein kinase Rp-8-pCPTcGMPS (291). Constitutive expression of cGMP-dependent protein kinase in mesangial cells also prevented induction of TSP1 expression in mesangial cells (293).…”
Section: E No Regulation Of Tsp1 Expressionsupporting
confidence: 80%
“…7,30,35,36,38,39,53,54 In the present studies, we addressed whether selective targeting of only TGF-␤ activated by TSP1 would be an effective approach to reduce renal dysfunction in a mouse model of type 1 diabetes. These studies showed that i.p.…”
Section: Discussionmentioning
confidence: 99%
“…The increased oxidative stress under high glucose conditions stimulates increased TSP1 protein expression by mesangial cells due to decreased nitric oxide-protein kinase G-mediated transcriptional repression and increased expression of the transcription factor USF2. 30,31 Glucose also increases TSP1 expression by podocytes, 32 and angiotensin II also increases TSP1 expression by renal mesangial cells and cardiac and renal interstitial cells in vitro, which results in increased TGF-␤ activity. 7,31,33 There is also evidence that TSP1-mediated latent TGF-␤ activation is involved in the development of diabetic nephropathy: TSP1 protein is increased in the glomeruli of patients with types 1 and 2 diabetic nephropathy, which correlates with increased TGF-␤ activity.…”
mentioning
confidence: 96%